Association of School Characteristics and Implementation in the X:IT Study—A School‐Randomized Smoking Prevention Program. (May 2017) - Bast, Lotus S.; Due, Pernille; Ersbøll, Annette K.; Damsgaard, Mogens T.; Andersen, Anette
ABSTRACT: BACKGROUND: Assessment of implementation is essential for the evaluation of school‐based preventive activities. Interventions are more easily implemented in schools if detailed instructional manuals, lesson plans, and materials are provided; however, implementation may also be affected by other factors than the intervention itself—for example, school‐level characteristics, such as principal support and organizational capacity. We examined school‐level characteristics of schools in groups of high, medium, and low implementation of a smoking prevention intervention. METHODS: The X:IT study is a school‐randomized trial testing a multicomponent intervention to prevent smoking among adolescents. Our data came from electronic questionnaires completed by school coordinators at 96.1% of participating intervention schools (N = 49) at first follow ‐up. RESULTS: Schools that implemented the X:IT intervention to a medium or high degree had higher levels of administrative leadership (77.3% and 83.3% vs 42.9%), school climate/organizational health (95.5% and 91.7% vs 66.7%), mission‐policy alignment (90.9% and 100.0% vs 71.4%), personnel expertise (81.8% and 75.0% vs 46.7%), school culture (77.3% and 91.7% vs 53.3%), positive classroom climate (91.4% and 96.2% vs 82.9%) compared with low implementation schools. CONCLUSION: Our findings highlight the importance of considering the school context in future health prevention initiatives.